Challenges in Palliative Care Research: Experience from a Randomized Controlled Trial in Refractory Cancer Cachexia - Joanne Reid; David Scott; Sam Porter (Palliative Medicine and Hospice Care, 2015)
There is a paucity of research studies in palliative care with less than 1% of clinical trials being relevant to the hospice and palliative care setting.1 Difficulties in conducting studies with this client group such as recruitment, retention, methodological and ethical issues are well documented within the literature.